The Efficacy and Safety of Intrathecal Autologous Bone Marrow-Derived Mesenchymal Stromal Cells in Amyotrophic Lateral Sclerosis: A Pilot Study - Gholamreza Shamsaei; Fatemeh Houshmand; Ahmad Ahmadzadeh Deylami; Armita Valizadeh; Shahram Rafie; Maryam Moradi (Tabriz University of Medical Sciences, 2023)
Purpose: Amyotrophic lateral sclerosis (ALS) is an uncommon and aggressive neurodegenerative disorder that influences the lower and upper motor neurons. There are low eligible drugs for ALS treatment; in this regard, supplemental and replacement treatments are essential. There are relative studies in the field of mesenchymal stromal cells (MSCs) therapy in ALS, but the different methods, differently used medium, and difference in follow-up periods affect the outcome treatment. Methods: The current survey is a single-center, phase I clinical trial to evaluating the efficacy and safety of autologous bone marrow (BM)-derived MSCs through intrathecal administration in ALS patients. MNCs were isolated from BM specimens and cultured. The clinical outcome was evaluated based Revised Amyotrophic Lateral Sclerosis Functional Rating (ALSFRS-R) Scale. Results: Each patient received 15±3×106 cells through subarachnoid space. No adverse events (AEs) were detected. Just one patient experienced a mild headache after injection. Following injection, no new intradural cerebrospinal pathology transplant-related was observed. None of the patients' pathologic disruptions following transplantation were detected by magnetic resonance imaging (MRI). The additional analyses have shown the average rate of ALSFRS-R score and forced vital capacity (FVC) reduction have decreased during 10 months following MSCs transplantation versus the pretreatment period, from -5.4±2.3 to -2±3.08 ALSFRS-R points/period (P=0.014) and -12.6±5.22% to -4.8±14.72%/period (P<0.001), respectively. Conclusion: These results have shown that autologous MSCs transplantation reduces the disease's progression and has favorable safety. Trial Registration: This study performed as a phase I clinical trial (code IRCT20200828048551N1).